Evaluation of Antioxidant Enzymes Activity and Malondialdehyde Levels in Patients With Chronic Periodontitis and Diabetes Mellitus. Issue 5 (1st May 2014) - Trivedi, Shilpa; Lal, Nand; Mahdi, Abbas Ali; Mittal, Madhukar; Singh, Babita; Pandey, Shivani
Abstract : Background: The aim of this study is to investigate the impact of diabetes, a known risk factor for periodontitis, on activities of antioxidant enzymes superoxide dismutase (SOD), glutathione reductase (GR), and catalase (CAT) as well as levels of free radical damage marker malondialdehyde (MDA) in blood and saliva of individuals with chronic periodontitis (CP). Methods: Sixty patients with CP (30 patients with type 2 diabetes mellitus [DMCP] and 30 systemically healthy patients [CP]) and 60 periodontally healthy individuals (30 patients with type 2 diabetes mellitus and 30 systemically healthy patients [PH]) were included in this study. After clinical measurements, blood and saliva samples were collected. SOD, GR, and CAT activities in red blood cell lysate and saliva and MDA levels in plasma and saliva samples were spectrophotometrically assayed. An analysis of variance test followed by a post hoc test was used to compare the intragroup and intergroup variances among the study groups. Results: MDA levels in both the periodontitis groups were higher than in the periodontally healthy groups, but the difference between the CP and DMCP groups did not reach statistical significance ( P >0.05). There was a highly significant difference between the CP and PH groups for all the enzymes studied except for SOD in blood. Only salivary SOD and GR activities were significantly different in the CP and DMCP groups. Conclusions: This study favors the role of oxidative stress in both diabetes and periodontitis. It shows that the compensatory mechanism of the body is partially collapsed because of excessive production of free radicals during periodontitis and is not able to cope with increased free radical generation attributable to diabetes, thereby worsening the situation.